Marriage In The Period Of ' Iddah Perspective Radical FeminismKate Millett: (Case Study in the village of Gunung Malang, District Sumberjambe, Jember Regency East Java) - Awaliya Safithri; Hasbi Ash Shiddiqi (FORPIM PTKIS ZONA TAPAL KUDA, 2022)
ABSTRACTMarriage in the period of ' iddah is a rare phenomenon. However, in some areas such marriages often occur, such as in Gunung Malang Village, Jember. In this case the perspective of radical feminism is used to provide an objective assessment . The purpose of this study was to determine the factors behind the husband and the wife carry out the marriage age ' iddah which occurred in the village of Gunung Malang and analyzing the views of religious leaders and the public about the mating period ' iddah in villages that Kate Millett's radical feminism perspective .The approach used in this study is a descriptive-qualitative approach to feminism with the type of field research.Results of research 1. Some factors behind the occurrence of marriage ' idda that occurred in the village of Gunung Malang d iantaranya are economic factors , tradition (long-term ' iddah died one hundred days ), understanding of religion mini m, emotional concerns that women will be the status of widows , internal environment ( family ), and external environment (a decision from the men to women to get married ) . 2. The existence of institutions that support patriarchal culture, including ideological , social classes, economics and education , psychology , and sociology. Can be analyzed that in practice, marriage period 'iddah actually supports the culture of the patriarchy with the existence of these five institutions. So it is reviewed with the view of Kate Millett, Marriage that occurred during 'iddah has violated the values of equality because almost women do not have a role.Keywords: Marriage, ' Iddah , Kate Millett, Radical Feminism